PERENCANAAN STRUKTUR GEDUNG LABORATORIUM TEKNIK ELEKTRO DAN TEKNIK PERENCANAAN WILAYAH - Astry Selfiyana; Tira Roesdiana (Journal of Research and Inovation in Civil Engineering as Applied Science, 2023)
The laboratory has an important role in supporting academic/non-academic activities, especially at the Faculty of Engineering, Universitas Swadaya Gunung Jati Cirebon. Along with the development of departments at the Faculty of Engineering, it is necessary to increase laboratory facilities are needed which are designed separately to facilitate educational activities. This study aims to plan and design the structure of the Electrical Engineering Laboratory and Urban Regional Planning Engineering building with a reinforced concrete structure type consisting of 4 floors with a floor height of 4 m. This building was built on Jl.Perjuangan (Additional Building Area), Sunyaragi, Kec. Kesambi, Cirebon City with a hard soil type which according to the earthquake resistance planning regulations for buildings (SNI 1726-2019) is included in the seismic design category D. The design of this building uses a special moment resisting frame system (SRPMK). The structural planning of this building includes plates, beams, columns and foundations following the reinforced concrete structural regulations (SNI 2847-2019). The earthquake load was calculated using the response spectrum method and then analyzed using the ETABS computer aided program